Avaliação da extensão universitária: caminhos, desafios e possibilidades - Silva, Luciane Duarte (2022)
This research has the general objective of identifying possibilities of evaluation of Extension actions that can be used as references by course coordinators and professors in Higher Education Institutions, contemplating their main foundations, concepts and theoretical construction. The justification for this study stems from the transformations that are occurring in the educational sector in relation to the theme due to Resolution No. 7 of 2018 from the Ministry of Education and the consequent mobilization of all ICES to meet its guidelines. Besides the implementation of the curricularization of extension, another challenge that arises in this process is the evaluation of extensionist actions. The present work presents the following problematic question: "what are the possibilities and challenges in the evaluation of Extension actions that can be used as references by course coordinators and professors in Higher Education Institutions in their extensionist actions"? Taking as reference the following documents: (a) Resolution nº7 of 2018 (BRASIL, 2018), (b) the National Policy of Extension of the Forum of Pro-Rectors of Extension of Brazilian Public Institutions of Higher Education (FORPROEX, 2012), (c) the Referentials for the construction of a National Policy of Extension in ICES (FOREXT, 2013) and (d) documents and academic works found in the bibliographic and documentary review, referring to the period from 2015 to 2020 on the theme: Evaluation of University Extension. This research considers the hypothesis that the exploratory survey through documentary research assists in the construction of benchmarks for the evaluation process of extension actions in Higher Education Institutions. From the paths that the type of qualitative research outlines, the methodology of this study is composed of the following methods: exploratory research subsidized by bibliographic and documental research and later descriptive analysis. The review of previous studies related to the proposed theme focused on the period between 2015 and 2020, in theses, dissertations and scientific articles and books on the subject of University Extension. The research was restricted to publications in English, Spanish and Portuguese languages, considering research available in the following online bases: (a) Bank of Theses and Dissertations of the Methodist University of São Paulo; (b) Brazilian Digital Library of Theses and Dissertations (BDTD); (c) National Network of University Extension - RENEX; (e) Iberoamerican Congress and Brazilian Congress of University Extension; (f) specific books on university extension... The results described in the research contribute to a greater understanding of the historical evolution of the theme and indicate paths for the evaluation processes of extension, especially for teachers and coordinators of undergraduate courses in higher education.(AU)